Sosialisasi Strategi Technopreneurship pada Siswa Paket C Di Pusat Kegiatan Belajar Masyarakat (PKBM) Yabes Medan (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2022)
Technopreneurship is not only beneficial in the development of large and sophisticated industries, but can also be directed to provide benefits to people who have weak economic abilities and to improve the quality of life. This activity aims to increase the awareness of Package C students at the Pusat Kegiatan Belajar Masyarakat (PKBM) Yabes Medan  to develop their entrepreneurship based on technology by utilizing existing technology. This socialization method was carried out through lectures and questions and answers which was held on August 19-20, 2022. The scope of this activity was carried out at the Pusat Kegiatan Belajar Masyarakat (PKBM) Yabes Medan  with the participants being students of Package C PKBM Yabes Medan. The results of this socialization show that based on the results of the questionnaire given to participants, the success rate is stated to be 100%. Where during pre-socialization the participants did not understand well about technopreneurship both in theory and practice. After the socialization, the participants understood well about technopreneurship both in theory and practice. The conclusion of this activity is that the participants feel that this rehearsal activity is useful, because the participants are aware of the lack of literacy related to increasing interest in entrepreneurship with the technopreneurship method and the participant's response to this service activity states that the delivery of the material is good and the participants understand the explanation given. This is shown by the interactive atmosphere between the participants and the service team.